NF-loaded high-valence metal doped nickel-iron-zinc-cerium-cobalt (oxygen) hydroxide bifunctional catalyst, and preparation method and application thereof
By loading high-valent metal doped with nickel iron zinc cerium cobalt (oxygen) hydroxide catalyst on nickel foam, a nanoflower structure is formed, which solves the problem of slow kinetics of oxygen evolution and urea oxidation reaction in electrolytic water, and achieves the catalytic activity and stability of efficient electrolytic water production and urea oxidation.
Patent Information
- Application Number
- CN202510768549.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-10
- Publication Date
- 2025-08-22
AI Technical Summary
In the existing electrolytic technology, the kinetics of the oxygen evolution reaction and urea oxidation reaction are slow, and the catalyst is costly and has limited durability, making it difficult to achieve efficient electrolytic hydrogen production and wastewater purification under complex working conditions.
High-valent metal doped with nickel iron zinc cerium cobalt (oxygen) hydroxide catalyst is used to form a nanoflower structure by loading high-valent metals on nickel foam, optimizing catalytic active sites and electronic structures, and improving conductivity and stability.
It has achieved efficient catalytic activity and a wide range of application in the fields of electrolytic hydrogen production and urea oxidation, reducing costs, improving the stability of the catalyst and electron transport efficiency.
Smart Images

Figure CN120519908A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of high entropy electrocatalysts, and specifically relates to a NF-supported high-valent metal-doped nickel-iron-zinc-cerium-cobalt (oxy) hydroxide bifunctional catalyst, a preparation method, and an application thereof. Background Art
[0002] In the water electrolysis system, the oxygen evolution reaction (OER) is an anode half-reaction involving a complex process of four-electron transfer. It has problems such as slow reaction kinetics and high overpotential, which limits the overall electrolysis efficiency. To address this problem, the electrocatalytic urea oxidation reaction (UOR) has a lower thermodynamic potential (0.37V lower than OER and 70% less energy consumption) and can simultaneously purify urea-containing wastewater, making it an ideal anode reaction to replace OER. However, UOR involves a six-electron transfer process and also faces the challenge of sluggish kinetics. In addition, the urea concentration in actual wastewater fluctuates and the electrolyte composition is complex, which places higher requirements on the universality and stability of the catalyst. Coupling UOR with the hydrogen evolution reaction (HER) to construct an efficient electrocatalytic system is a key direction to break through the bottleneck of traditional water electrolysis technology.
[0003] Currently, noble metal derivatives such as iridium and ruthenium are considered benchmark catalysts for OER and UOR due to their excellent catalytic activity. However, their high cost and limited durability severely restrict their large-scale application. Therefore, the development of low-cost, highly active non-noble metal electrocatalysts has become a research hotspot. Nickel- and iron-based materials, due to their abundant reserves and excellent catalytic performance, show broad application prospects in water electrolysis.
[0004] While research has made progress in the design of high-entropy electrocatalysts, optimizing the active site structure, improving electron transfer efficiency, and enhancing catalyst durability for the complex OER and UOR bifunctional catalysis remain pressing technical challenges. Developing bifunctional electrocatalysts with high catalytic activity, high stability, and a wide range of applications is of great practical significance for promoting low-cost hydrogen production from water electrolysis and wastewater resource utilization.
[0005] Application Contents
[0006] Based on the technical problems involved above, the purpose of this application is to provide a high-valent metal-doped nickel-iron-zinc-cerium-cobalt (oxy) hydroxide catalyst, preparation method and application, so as to develop a bifunctional electrocatalyst with high catalytic activity, high stability and wide application range, which can be used in the field of hydrogen production by electrolysis of water and in the field of urea oxidation.
[0007] On the one hand, the present application provides a method for preparing a high-valent metal-doped nickel-iron-zinc-cerium-cobalt (oxy) hydroxide catalyst, comprising the following steps:
[0008] The metal salt, urea and polyvinylpyrrolidone (PVP) are uniformly mixed in deionized water to obtain a mixed solution in a uniform state, i.e., a pre-product;
[0009] The pre-product is transferred to a high-pressure reactor, and nickel foam (NF) is added and impregnated for about 1 to 2 hours until the pre-product is fully dispersed into the NF three-dimensional porous structure; then the reaction is carried out at a temperature of 100 to 160° C. for 4 to 10 hours to obtain product I;
[0010] The product I is centrifuged, washed, and vacuum-dried to obtain a NF-supported high-valent metal-doped NiFeZnCeCo (oxy)hydroxide material, namely, M-NiFeZnCeCoOOH / NF (M=Cr, V, Mo) bifunctional catalyst;
[0011] The metal salts include: a high-valent metal source, a trivalent iron source, a divalent cobalt source, a divalent nickel source, a divalent zinc source and a trivalent cerium source;
[0012] The molar volume ratio of the high-valent metal source, ferric iron source, divalent cobalt source, divalent nickel source, divalent zinc source, trivalent cerium source, urea, polyvinyl pyrrolidone (PVP) and deionized water is (0-0.5) mmol: (0-1) mmol: (0-1) mmol: (0-1) mmol: (0-1) mmol: (0-1) mmol: (4-7) mmol: (0.5-0.9) mmol: (10-100) mL, wherein the amount of at least one of the high-valent metal source, ferric iron source, divalent cobalt source, divalent nickel source, divalent zinc source and trivalent cerium source is not 0.
[0013] The preparation method of the present application adopts the above-mentioned raw materials, ratios and reaction conditions to successfully obtain nickel foam (NF)-loaded high-valent metal-doped NiFeZnCeCo (oxy)hydroxide material (M-NiFeZnCeCoOOH / NF (M=Cr, V, Mo)).
[0014] In some optional embodiments, the high-valent metal source includes a trivalent chromium source, a trivalent vanadium source and a hexavalent molybdenum source, and the molar amounts of the trivalent chromium source, the trivalent vanadium source and the hexavalent molybdenum source are (0-0.5) mmol, (0-1) mmol and (0-1) mmol, respectively.
[0015] In some optional embodiments, the molar ratio of the polyvinyl pyrrolidone to the urea is 0.675 mmol:4 mmol.
[0016] In some optional embodiments, the product I is centrifugally washed and vacuum dried, specifically: the product is first washed 3 times with ethanol, then washed 3 times with deionized water, and then dried in a vacuum drying oven at 60-80°C for 10-12 hours.
[0017] In some optional embodiments, the solid-liquid ratio of the high-valent metal salts of chromium, molybdenum, and vanadium: nickel, iron, zinc, cerium, and cobalt metal salts: urea: PVP: deionized water is (0.1-0.2) mmol: (1-5) mmol: (3-5) mmol: (0.06-0.08) mmol: (14.4-25.2) ml, wherein the amount of at least one high-valent metal salt of chromium, molybdenum, and vanadium is not 0.
[0018] On the other hand, the present application provides a NF-supported high-valent metal-doped nickel-iron-zinc-cerium-cobalt (oxy)hydroxide bifunctional electrocatalyst, which is prepared by any of the aforementioned preparation methods.
[0019] On the other hand, the present application also provides an application of a NF-supported high-valent metal-doped nickel-iron-zinc-cerium-cobalt (oxy)hydroxide bifunctional electrocatalyst in the electrolysis of water to produce hydrogen.
[0020] On the other hand, the present application also provides an application of a NF-supported high-valent metal-doped nickel-iron-zinc-cerium-cobalt (oxy)hydroxide bifunctional electrocatalyst in urea electrolysis.
[0021] Through the preparation method of the present application, a high-valent metal-doped NiFeZnCeCo (oxy) hydroxide material (M-NiFeZnCeCoOOH / NF (M=Cr, V, Mo)) supported on nickel foam (NF) was successfully obtained. The reaction conditions are mild and controllable, with good reproducibility and strong practicality. The synergistic effect between multiple metals accelerates charge transfer, and different electronegativity adjusts the electronic structure and charge density of the material; high-valent metal doping can effectively improve the conductivity of the material, adjust the electron density around the high-valent metal (Cr, V, Mo), and optimize the inherent catalytic activity of the catalyst; the nanostructure has a larger specific surface area and can expose more active sites. The synthesized high-valent metal-doped nickel-iron-zinc-cerium-cobalt (oxy) hydroxide supported on nickel foam (NF) has excellent hydrogen evolution, oxygen evolution, urea reaction activity and stability, and can be used in the field of hydrogen production by water electrolysis, as well as in the field of urea oxidation, with a wide range of applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] The accompanying drawings are used to provide a further understanding of the present application and constitute a part of the specification. Together with the following detailed description, they are used to explain the present application but do not constitute a limitation of the present application. In the accompanying drawings:
[0023] Figure 1 This is an X-ray powder diffraction analysis pattern (XRD) of a high-valent metal-doped nickel-iron-zinc-cerium-cobalt (oxy)hydroxide catalyst obtained in Example 1 and Example 6 of the present application;
[0024] Figure 2This is a morphology analysis (SEM) of the high-valent metal Cr-doped NiFeZnCeCoOOH / NF material obtained in Example 1 of this application;
[0025] Figure 3 Linear sweep voltammetry (LSV) curves comparing the hydrogen evolution reaction performance of the high-valent metal-doped nickel-iron-zinc-cerium-cobalt (oxy)hydroxide catalyst materials obtained in exemplary embodiments 1 to 10 of the present application in 1M KOH;
[0026] Figure 4 Linear sweep voltammetry (LSV) curves comparing the oxygen evolution reaction performance of the high-valent metal-doped nickel-iron-zinc-cerium-cobalt (oxy)hydroxide catalyst materials obtained in exemplary embodiments 1 to 10 of the present application in 1M KOH;
[0027] Figure 5 For exemplary embodiments 1 to 10 of the present application, linear sweep voltammetry (LSV) curves of urea oxidation reaction of high-valent metal-doped nickel, iron, zinc, cerium, and cobalt (oxy) hydroxide catalyst materials in 1 M KOH + 0.33 M Urea were obtained;
[0028] Figure 6 For the purposes of Exemplary Examples 1 to 10 of this application, linear sweep voltammetry (LSV) curves of urea oxidation reaction of high-valent metal-doped nickel-iron-zinc-cerium-cobalt (oxy)hydroxide catalyst material in 1 M KOH + 0.33 M Urea were obtained. DETAILED DESCRIPTION
[0029] The present application will be further described below in conjunction with specific examples. It should be understood that these embodiments are only intended to illustrate the present application and are not intended to limit the scope of the present application. In addition, it should be understood that after reading the contents taught in this application, those skilled in the art may make various changes or modifications to the present application, and these equivalent forms also fall within the scope defined by the claims appended hereto.
[0030] Example 1
[0031] The synthesis method of Cr (30 mg)-doped NiFeZnCeCoOOH / NF bifunctional catalyst comprises the following steps:
[0032] 0.03g Cr(NO3)3·9H2O, 0.404g Fe(NO3)3·9H2O, 0.291g Co(NO3)2·6H2O, 0.291g Ni(NO3)2·6H2O, 0.288g Zn(NO3)2·6H2O, 0.434g Ce(NO3)3·6H2O, 0.24g urea, and 0.075g PVP were weighed into a 100mL beaker. 20mL of deionized water and a magnet were added. The mixture was stirred at an appropriate speed on a magnetic stirrer for 10 minutes and then sonicated to completely dissolve until homogeneous, yielding a pre-product. The pre-product was then transferred to a 50mL autoclave and pretreated nickel foam (NF) was added. The mixture was immersed for approximately 1–2 hours until the pre-product was fully dispersed into the NF's three-dimensional porous structure. The mixture was then hydrothermally reacted in an oven at 100°C for 8 hours. The sample was washed three times with ethanol and deionized water, picked up with tweezers and evenly placed in a Petri dish, covered with plastic wrap, and then evenly pierced with tweezers. The sample was placed in a vacuum drying oven set at 60°C and dried for 10 hours to obtain 30Cr-NiFeZnCeCoOOH / NF material.
[0033] Example 2
[0034] The synthesis method of Cr (15 mg)-doped NiFeZnCeCoOOH / NF bifunctional catalyst comprises the following steps:
[0035] 0.015g Cr(NO3)3·9H2O, 0.404g Fe(NO3)3·9H2O, 0.291g Co(NO3)2·6H2O, 0.291g Ni(NO3)2·6H2O, 0.288g Zn(NO3)2·6H2O, 0.434g Ce(NO3)3·6H2O, 0.24g urea, and 0.075g PVP were weighed into a 100mL beaker. 20mL of deionized water and a magnet were added. The mixture was stirred on a magnetic stirrer at an appropriate speed for 10 minutes and then sonicated to completely dissolve until homogeneous, yielding a pre-product. The solution was then transferred to a 50mL autoclave and pretreated nickel foam (NF) was added. The mixture was immersed for approximately 1–2 hours until the pre-product was fully dispersed into the NF's three-dimensional porous structure. The mixture was then hydrothermally reacted in an oven at 100°C for 8 hours. The sample was washed three times with ethanol and deionized water, picked up with tweezers and evenly placed in a Petri dish, covered with plastic wrap, and then evenly pierced with tweezers. The sample was placed in a vacuum drying oven set at 60°C and dried for 10 hours to obtain 15Cr-NiFeZnCeCoOOH / NF material.
[0036] Example 3
[0037] The synthesis method of Cr (45 mg)-doped NiFeZnCeCoOOH / NF bifunctional catalyst comprises the following steps:
[0038] 0.045g Cr(NO3)3·9H2O, 0.404g Fe(NO3)3·9H2O, 0.291g Co(NO3)2·6H2O, 0.291g Ni(NO3)2·6H2O, 0.288g Zn(NO3)2·6H2O, 0.434g Ce(NO3)3·6H2O, 0.24g urea, and 0.075g PVP were weighed into a 100mL beaker. 20mL of deionized water and a magnet were added. The mixture was stirred on a magnetic stirrer at an appropriate speed for 10 minutes and then sonicated to completely dissolve until homogeneous, yielding a pre-product. The pre-product was then transferred to a 50mL autoclave and pretreated nickel foam (NF) was added. The pre-product was immersed for approximately 1–2 hours until it was fully dispersed into the NF's three-dimensional porous structure. The product was then hydrothermally reacted in an oven at 100°C for 8 hours. The sample was washed three times with ethanol and deionized water, picked up with tweezers and evenly placed in a Petri dish, covered with plastic wrap, and then evenly pierced with tweezers. The sample was placed in a vacuum drying oven set at 60°C and dried for 10 hours to obtain 45Cr-NiFeZnCeCoOOH / NF material.
[0039] Example 4
[0040] The synthesis method of V (30 mg) doped NiFeZnCeCoOOH / NF bifunctional catalyst comprises the following steps:
[0041] 0.03g VCl3, 0.404g Fe(NO3)3·9H2O, 0.291g Co(NO3)2·6H2O, 0.291g Ni(NO3)2·6H2O, 0.288g Zn(NO3)2·6H2O, 0.434g Ce(NO3)3·6H2O, 0.24g urea, and 0.075g PVP were weighed and placed in a 100mL beaker. 20mL of deionized water and a magnet were added. The mixture was stirred at an appropriate speed on a magnetic stirrer for 10 minutes and then sonicated to completely dissolve until uniform, yielding a pre-product. The pre-product was then transferred to a 50mL autoclave and pretreated nickel foam (NF) was added. The mixture was immersed for approximately 1-2 hours until the pre-product was fully dispersed into the NF's three-dimensional porous structure. The mixture was then hydrothermally reacted in an oven at 100°C for 8 hours. The sample was washed three times with ethanol and deionized water, picked up with tweezers and evenly placed in a Petri dish, covered with plastic wrap, and then evenly pierced with tweezers. The sample was placed in a vacuum drying oven set to 60°C and dried for 10 hours to obtain 30V-NiFeZnCeCoOOH / NF material.
[0042] Example 5
[0043] The synthesis method of Mo (30 mg) doped NiFeZnCeCoOOH / NF bifunctional catalyst comprises the following steps:
[0044] 0.03g NaMoO4·2H2O, 0.404g Fe(NO3)3·9H2O, 0.291g Co(NO3)2·6H2O, 0.291g Ni(NO3)2·6H2O, 0.288g Zn(NO3)2·6H2O, 0.434g Ce(NO3)3·6H2O, 0.24g urea, and 0.075g PVP were weighed into a 100mL beaker. 20mL of deionized water and a magnet were added. The mixture was stirred on a magnetic stirrer at an appropriate speed for 10 minutes and then sonicated to completely dissolve until homogeneous, yielding a pre-product. The pre-product was then transferred to a 50mL autoclave and pretreated nickel foam (NF) was added. The mixture was immersed for approximately 1–2 hours until the pre-product was fully dispersed into the NF's three-dimensional porous structure. The mixture was then hydrothermally reacted in an oven at 100°C for 8 hours. The sample was washed three times with ethanol and deionized water, picked up with tweezers and evenly placed in a Petri dish, covered with plastic wrap, and then evenly pierced with tweezers. The sample was placed in a vacuum drying oven set at 60°C and dried for 10 hours to obtain 30Mo-NiFeZnCeCoOOH / NF material.
[0045] Example 6
[0046] The synthesis method of NiFeZnCeCoOOH / NF bifunctional catalyst comprises the following steps:
[0047] 0.404g Fe(NO3)3·9H2O, 0.291g Co(NO3)2·6H2O, 0.291g Ni(NO3)2·6H2O, 0.288g Zn(NO3)2·6H2O, 0.434g Ce(NO3)3·6H2O, 0.24g urea, and 0.075g PVP were weighed into a 100mL beaker. 20mL of deionized water and a magnet were added. The mixture was stirred at an appropriate speed on a magnetic stirrer for 10 minutes and then sonicated to completely dissolve until homogeneous, yielding a pre-product. The pre-product was then transferred to a 50mL autoclave and pretreated nickel foam (NF) was added. The pre-product was immersed for approximately 1-2 hours until it was fully dispersed into the NF's three-dimensional porous structure. The product was then hydrothermally reacted in an oven at 100°C for 8 hours. The sample was washed three times with ethanol and deionized water, picked up with tweezers and evenly placed in a Petri dish, covered with plastic wrap, and then evenly pierced with tweezers. The sample was placed in a vacuum drying oven set at 60°C and dried for 10 hours to obtain NiFeZnCeCoOOH / NF material.
[0048] Example 7
[0049] The synthesis method of NiFeZnCeOOH / NF bifunctional catalyst comprises the following steps:
[0050] 0.404g Fe(NO3)3·9H2O, 0.291g Ni(NO3)2·6H2O, 0.288g Zn(NO3)2·6H2O, 0.434g Ce(NO3)3·6H2O, 0.24g urea, and 0.075g PVP were weighed into a 100mL beaker. 20mL of deionized water and a magnet were added. The mixture was stirred at an appropriate speed on a magnetic stirrer for 10 minutes. Ultrasonic treatment was then performed to completely dissolve the mixture until it reached a homogeneous state, yielding a pre-product. The pre-product was then transferred to a 50mL autoclave and pretreated nickel foam (NF) was added. The mixture was immersed for approximately 1-2 hours until the pre-product was fully dispersed into the NF's three-dimensional porous structure. The mixture was then hydrothermally reacted in an oven at 100°C for 8 hours. The sample was washed three times with ethanol and deionized water, picked up with tweezers and evenly placed in a Petri dish, covered with plastic wrap, and then evenly pierced with tweezers. The sample was placed in a vacuum drying oven set at 60°C and dried for 10 hours to obtain NiFeZnCeOOH / NF material.
[0051] Example 8
[0052] The synthesis method of NiFeZnOOH / NF bifunctional catalyst comprises the following steps:
[0053] 0.404g Fe(NO3)3·9H2O, 0.291g Ni(NO3)2·6H2O, 0.288g Zn(NO3)2·6H2O, 0.24g urea, and 0.075g PVP were weighed into a 100mL beaker. 20mL of deionized water and a magnet were added. The mixture was stirred at an appropriate speed on a magnetic stirrer for 10 minutes. Ultrasonic treatment was then performed to completely dissolve the mixture until it reached a uniform state, yielding a pre-product. The pre-product was then transferred to a 50mL autoclave and pretreated nickel foam (NF) was added. The mixture was immersed for approximately 1-2 hours until the pre-product was fully dispersed into the NF's three-dimensional porous structure. The mixture was then hydrothermally reacted in an oven at 100°C for 8 hours. The sample was washed three times with ethanol and deionized water, picked up with tweezers and evenly placed in a Petri dish, covered with plastic wrap, and then evenly pierced with tweezers. The sample was placed in a vacuum drying oven set at 60°C and dried for 10 hours to obtain NiFeZnOOH / NF material.
[0054] Example 9
[0055] The synthesis method of NiFeOOH / NF bifunctional catalyst comprises the following steps:
[0056] 0.404g Fe(NO3)3·9H2O, 0.291g Ni(NO3)2·6H2O, 0.24g urea, and 0.075g PVP were weighed into a 100mL beaker, followed by 20mL of deionized water and a magnetic stirrer. The mixture was stirred at an appropriate speed for 10 minutes and then sonicated to completely dissolve until homogeneous, yielding a pre-product. The pre-product was then transferred to a 50mL autoclave and pretreated nickel foam (NF) was added. The pre-product was immersed for approximately 1-2 hours until the pre-product was fully dispersed into the NF's three-dimensional porous structure. The product was then hydrothermally reacted in an oven at 100°C for 8 hours. The sample was washed three times with ethanol and deionized water. The sample was picked up with tweezers and evenly placed in a Petri dish. The dish was covered with plastic wrap and several holes were evenly pierced with tweezers. The sample was then dried in a vacuum oven at 60°C for 10 hours to yield the NiFeOOH / NF material.
[0057] Example 10
[0058] The synthesis method of NiOOH / NF bifunctional catalyst comprises the following steps:
[0059] 0.291g Ni(NO₃)₂·6H₂O, 0.24g urea, and 0.075g PVP were weighed into a 100mL beaker, followed by 20mL of deionized water and a magnet. The mixture was stirred at an appropriate speed on a magnetic stirrer for 10 minutes and then sonicated to completely dissolve until homogeneous, yielding a pre-product. The pre-product was then transferred to a 50mL autoclave and pretreated nickel foam (NF) was added. The mixture was immersed for approximately 1-2 hours until the pre-product was fully dispersed into the NF's three-dimensional porous structure. The reaction was then hydrothermally reacted in an oven at 100°C for 8 hours. The sample was washed three times with ethanol and deionized water. The sample was picked up with tweezers and evenly placed in a Petri dish. The dish was covered with plastic wrap and several holes were evenly pierced with tweezers. The sample was then dried in a vacuum oven at 60°C for 10 hours to yield the NiOOH / NF material.
[0060] The raw materials and amounts used in the above examples are summarized in the following table:
[0061]
[0062] Step 1 in the above implementation case is only an exemplary operation, and a large industrial stirred reactor can be used to improve production efficiency and product quantity.
[0063] like Figure 1As shown, an XRD pattern of a high-valent metal chromium-doped nickel, iron, zinc, cerium, and cobalt (oxy)hydroxide catalyst was obtained using the method of the Reference Example. The figure shows that the presence of the (oxy)hydroxide is confirmed by diffraction peaks at 16.8°, 26.7°, and 46.4°, corresponding to the (200), (310), and (411) crystal planes of β-FeOOH (JCPDS: 34-1266), respectively.
[0064] like Figure 2 The 30Cr-NiFeZnCeCoOOH / NF shown in the figure exhibits a nanoflower morphology, which is composed of ultrathin nanosheets. The orderly arranged nanosheets form a three-dimensional structure, which can expose more active sites for adsorption / desorption of reaction intermediates.
[0065] like Figure 3 、 4 As shown in Figures 5 and 6, the materials obtained above are used as oxygen evolution, hydrogen evolution and urea oxidation electrode materials for hydrogen production by electrolysis of water. The polarization curve of the oxygen evolution reaction is tested using a three-electrode system, and the linear sweep voltammetry (LSV) curve of the oxygen evolution reaction is shown. Figure 3 The hydrogen evolution reaction (HER) activity of 30Cr-NiFeZnCeCoOOH / NF is shown in the figure. 2 The overpotential at this current density is only 250 mV, which shows excellent HER activity compared with other (oxy)hydroxides. Figure 4 Among them, 30Cr-NiFeZnCeCoOOH / NF showed the best catalytic performance at 100mA / cm 2 The overpotential at this current density is only 222 mV, which is better than NiFeZnCeCoOOH / NF (313 mV), 15Cr-NiFeZnCeCoOOH / NF (275 mV), 45Cr-NiFeZnCeCoOOH / NF (313 mV), 30V-NiFeZnCeCoOOH / NF (266 mV), and 30Mo-NiFeZnCeCoOOH / NF (304 mV). Figure 5 、 Figure 6 30Cr-NiFeZnCeCoOOH / NF at 100mA / cm 2 The lowest UOR starting potential (1.38V) was shown under the current density, which was better than NiFeZnCeCoOOH / NF (1.43V), 30V-NiFeZnCeCoOOH / NF (1.41V), and 30Mo-NiFeZnCeCoOOH / NF (1.52V). Figure 5 、 Figure 6), the introduction of urea resulted in a lower overpotential for 30Cr-NiFeZnCeCoOOH / NF, indicating that urea electrolysis improves hydrogen production efficiency. The nanoflower framework structure and high surface roughness formed by the high-valent metal facilitate the exposure of active sites and bubble desorption, improving catalytic efficiency and enhancing stability, enabling this application to achieve optimal catalytic performance.
[0066] The above description is merely an embodiment of the present application and does not limit the patent scope of the present application. Any equivalent structure or equivalent process transformation made using the description of the present application, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present application.
Claims
1. A method for preparing a NF-supported high-valent metal-doped nickel-iron-zinc-cerium-cobalt (oxy)hydroxide bifunctional electrocatalyst, characterized in that: The following steps are involved: uniformly mixing the metal salt, urea and polyvinyl pyrrolidone in deionized water to obtain a pre-product; The pre-product is transferred to a high-pressure reactor, NF is added for impregnation, and the reaction is carried out at a temperature of 100 to 160° C. for 4 to 10 hours to obtain product I; The product I is centrifuged, washed, and vacuum-dried to obtain a NF-supported high-valent metal-doped NiFeZnCeCo (oxy)hydroxide material, namely, M-NiFeZnCeCoOOH / NF (M=Cr, V, Mo) bifunctional catalyst; The metal salts include: a high-valent metal source, a trivalent iron source, a divalent cobalt source, a divalent nickel source, a divalent zinc source and a trivalent cerium source; The molar volume ratio of the high-valent metal source, ferric iron source, divalent cobalt source, divalent nickel source, divalent zinc source, trivalent cerium source, urea, polyvinyl pyrrolidone and deionized water is (0-0.5) mmol: (0-1) mmol: (0-1) mmol: (0-1) mmol: (0-1) mmol: (0-1) mmol: (4-7) mmol: (0.5-0.9) mmol: (10-100) mL; wherein, the amount of at least one of the high-valent metal source, ferric iron source, divalent cobalt source, divalent nickel source, divalent zinc source and trivalent cerium source is not 0.
2. The preparation method according to claim 1, wherein The high-valent metal source includes a trivalent chromium source, a trivalent vanadium source and a hexavalent molybdenum source, and the molar amounts of the trivalent chromium source, the trivalent vanadium source and the hexavalent molybdenum source are (0-0.5) respectively. mmol, (0~1)mmol and (0~1)mmol.
3. The preparation method according to claim 1, wherein The molar ratio of the polyvinyl pyrrolidone to the urea is 0.675:
4.
4. The preparation method according to claim 1, wherein The pre-product is in a uniform state.
5. The preparation method according to claim 1, wherein The added NF is impregnated until the pre-product is fully dispersed into the NF three-dimensional porous structure.
6. The preparation method according to claim 1, wherein The product I is centrifugally washed and vacuum dried, specifically: the product is first washed with ethanol three times, then washed with deionized water three times, and then dried in a vacuum drying oven at 60-80° C. for 10-12 hours.
7. The preparation method according to claim 1, wherein The solid-liquid ratio of the at least one high-valent metal salt of chromium, molybdenum, and vanadium: nickel, iron, zinc, cerium, and cobalt metal salt: urea: PVP: deionized water is (0.1-0.2) mmol: (1-5) mmol: (3-5) mmol: (0.06-0.08) mmol: (14.4-25.2) ml, wherein the amount of at least one high-valent metal salt of chromium, molybdenum, or vanadium is not zero.
8. A NF-supported high-valent metal-doped nickel-iron-zinc-cerium-cobalt (oxy)hydroxide bifunctional electrocatalyst prepared by the preparation method according to any one of claims 1 to 7.
9. Use of the NF-supported high-valent metal-doped nickel-iron-zinc-cerium-cobalt (oxy)hydroxide bifunctional electrocatalyst as claimed in claim 8 in hydrogen production by electrolysis of water.
10. Use of the NF-supported high-valent metal-doped nickel-iron-zinc-cerium-cobalt (oxy)hydroxide bifunctional electrocatalyst as claimed in claim 8 in urea electrolysis.